Tradition, Rationality, and Virtue: The Thought of Alasdair MacIntyre. By Thomas D. D’Andrea - Rothchild, Jonathan (The journal of theological studies, 2008)
It is truly a rare accomplishment to provide insight into the life and thought of a subtle philosopher. Plato's Dialogues shed light on Socrates the person and thinker, and recent works, such as Charles E. Reagan, Paul Ricoeur: His Life and Work (Chicago: University of Chicago Press, 1996) and Salomon Malka, Emmanuel Levinas: His Life and Legacy (Pittsburgh: Duquesne University Press, 2006), offer contemporary analogues. Thomas D. D’Andrea's in-depth study of Alasdair MacIntyre offers a comprehensive portrait of MacIntyre's dynamic intellectual development.